Herbicide carryover to various fall-planted cover crop species. (22nd August 2019) - Rector, Lucas S.; Pittman, Kara B.; Beam, Shawn C.; Bamber, Kevin W.; Cahoon, Charles W.; Frame, William H.; Flessner, Michael L.
Abstract: Residual herbicides applied to summer cash crops have the potential to injure subsequent winter annual cover crops, yet little information is available to guide growers' choices. Field studies were conducted in 2016 and 2017 in Blacksburg and Suffolk, Virginia, to determine carryover of 30 herbicides commonly used in corn, soybean, or cotton on wheat, barley, cereal rye, oats, annual ryegrass, forage radish, Austrian winter pea, crimson clover, hairy vetch, and rapeseed cover crops. Herbicides were applied to bare ground either 14 wk before cover crop planting for a PRE timing or 10 wk for a POST timing. Visible injury was recorded 3 and 6 wk after planting (WAP), and cover crop biomass was collected 6 WAP. There were no differences observed in cover crop biomass among herbicide treatments, despite visible injury that suggested some residual herbicides have the potential to effect cover crop establishment. Visible injury on grass cover crop species did not exceed 20% from any herbicide. Fomesafen resulted in the greatest injury recorded on forage radish, with greater than 50% injury in 1 site-year. Trifloxysulfuron and atrazine resulted in greater than 20% visible injury on forage radish. Trifloxysulfuron resulted in the greatest injury (30%) observed on crimson clover in 1 site-year. Prosulfuron and isoxaflutole significantly injured rapeseed (17% to 21%). Results indicate that commonly used residual herbicides applied in the previous cash crop growing season result in little injury on grass cover crop species, and only a few residual herbicides could potentially affect the establishment of a forage radish, crimson clover, or rapeseed cover crop.